Genres of polycode texts and their genre features - Odilova , Kamola (The Lingua Spectrum, 2025)
This article examines the genres and genre-specific characteristics of polycode texts, which transmit complex meanings by combining various semiotic resources such as sounds, images, and text. It emphasizes how these multimodal texts are changing modern communication on a variety of platforms, including social media, education, and advertising. The study highlights how crucial it is to comprehend polycode texts' structural traits and communicative purposes, especially in digital contexts. Polycode texts improve user engagement and information accessibility, as the author illustrates by examining examples such as infographics, instructional films, and social media posts. In addition, the article calls for new methods of teaching and evaluating multimodal compositions and explores the consequences for academic literacy and pedagogy. The significance of polycode texts on contemporary discourse is emphasized.